2018
DOI: 10.1002/mnfr.201800178
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Liquid Consumption Alters the Human Intestinal and Oral Microbiome

Abstract: ScopeGTPs (green tea polyphenols) exert anti‐CRC (colorectal cancer) activity. The intestinal microbiota and intestinal colonization by bacteria of oral origin has been implicated in colorectal carcinogenesis. GT modulates the composition of mouse gut microbiota harmonious with anticancer activity. Therefore, the effect of green tea liquid (GTL) consumption on the gut and oral microbiome is investigated in healthy volunteers (n = 12).Methods and results16S sequencing and phylogenetic investigation of communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 63 publications
(102 reference statements)
3
88
0
Order By: Relevance
“…As a result, we looked for factors which might affect the oral microbiome at a community level. Our primary confounders included oral hygiene and health, tobacco use, family history of NPC, and tea consumption ( 11 , 12 , 14 18 , 23 , 24 ). We also considered a history of oropharyngeal inflammation, the region where an individual lived, and alcohol use as covariates primarily expected to affect the microbiome, as well as salted fish consumption, which is primarily seen as a risk factor for NPC ( 13 , 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, we looked for factors which might affect the oral microbiome at a community level. Our primary confounders included oral hygiene and health, tobacco use, family history of NPC, and tea consumption ( 11 , 12 , 14 18 , 23 , 24 ). We also considered a history of oropharyngeal inflammation, the region where an individual lived, and alcohol use as covariates primarily expected to affect the microbiome, as well as salted fish consumption, which is primarily seen as a risk factor for NPC ( 13 , 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no studies describing the relationship between green tea consumption and the prevalence of pks + E. coli, one study has described the effects of green tea consumption on the gut microbiome. Yuan et al performed an intervention study in healthy Chinese adults and found a significant increase in the Firmicutes to Bacteroidetes ratio isolated from faecal matter after 2 weeks of green tea consumption (400 mL/day) 36 . Firmicutes and Bacteroidetes are two major bacterial phyla that dominate the human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering studies in mammals that focused on several oral bacteria at a time noted changes in oral microbiota with tea or tea extract consumption with consistent reductions in clostridium and increases in bifidobacterium and lactobacillus ( Table 3 ). Two recent human studies broadly examined oral microbiome at genus and species level, after GT or GT extract consumption [ 48 , 59 ]. The first study examined samples from two oral mucosal sites [ 59 , 60 ].…”
Section: Gt Extract and Gt Catechin Interactions With Oral And Gutmentioning
confidence: 99%
“…Two recent human studies broadly examined oral microbiome at genus and species level, after GT or GT extract consumption [ 48 , 59 ]. The first study examined samples from two oral mucosal sites [ 59 , 60 ]. The second examined saliva, a mixture of microbes shed from all mucosal and tooth surfaces [ 61 ].…”
Section: Gt Extract and Gt Catechin Interactions With Oral And Gutmentioning
confidence: 99%